2017
DOI: 10.1051/matecconf/201710304020
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting (RWH) and Groundwater Potential as Alternatives Water Resources in Malaysia: A Review

Abstract: Abstract. Socio-economic growth at present exerting pressure on the capacity of water supply. Water has been harvested worldwide since antiquity, thus, it is essential to manage the potential available of natural water supplies in the catchment to save water for dry periods when the supply-demand gap is comparatively high. The overall aim of this paper is to present a general overview of rainwater harvesting system and groundwater, and their potential applications for daily use. Many countries have implement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…One plausible explanation is that implementation strategies are difficult to evaluate and may coexist as a support to evidence-based interventions, making them an undesirable subject to address [11,12]. In conjunction to this, there is an absence of research evaluating RWH implementation strategies, despite previous research [13][14][15] revealed that they are poor. This indicates that research into fidelity by focusing on strategies is critical in RWH implementation.…”
Section: Intervention Fidelity and Implementation Fidelitymentioning
confidence: 99%
“…One plausible explanation is that implementation strategies are difficult to evaluate and may coexist as a support to evidence-based interventions, making them an undesirable subject to address [11,12]. In conjunction to this, there is an absence of research evaluating RWH implementation strategies, despite previous research [13][14][15] revealed that they are poor. This indicates that research into fidelity by focusing on strategies is critical in RWH implementation.…”
Section: Intervention Fidelity and Implementation Fidelitymentioning
confidence: 99%
“…The scavenging of air contaminants influences both the chemical composition and the pH of rainwater [9]. Acid precipitation is mostly caused by the anthropogenic sources such as sulfur oxides, and nitrogen oxides [6,10]. However, the acidity of rainwater depends on the relative contribution and neutralization of the major acidic and alkaline ions in atmosphere [3].…”
Section: Preliminarymentioning
confidence: 99%
“…Historically, rainwater harvesting has been practiced traditionally in many dry regions in the world as early as 4,500 B.C [10,11]. Currently, rainwater harvesting has been practiced in many countries for reducing reliance on the availability of domestic water from dams and reservoirs [12], supply non-potable water to building in urban areas [13], and solving water issues in semiarid regions for agricultural and domestic uses [14].…”
Section: The Quality Of Rainwater Harvestingmentioning
confidence: 99%
“…The impacts of climate change are difficult to predict, but regular floods and droughts and the associated shortages of available water resources may cause problems in the water supply system. Therefore, the development of alternative water sources, such as rainwater, reclaimed water, groundwater, and seawater desalination, has been researched as methods to prevent water shortages [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%